(Post) modern Islamic philosophy: challenges and perspectives - Bektovic, Safet (Islam and Christian-Muslim relations, 2012)
Islamic philosophy emerged and has been developed in a particular political and theological context, and its historical and present role cannot be examined independently of political and theological discourse. It is characteristic that some of the same questions that Muslims discussed in the early Middle Ages - the limits of human knowledge, the relationship between the divine and the human, the relationship between falsafa, kalām and fiqh, the role of political philosophy - have been taken up again, but in a new context. As in the past, relations between Muslims and non-Muslims, and especially inter-philosophical relationships, play a crucial role in present-day discussions too. This article seeks to shed light on the (post) modern possibilities and perspectives for Islamic philosophy within Islam and relating to contemporary Islamic discourse. It includes reference to the views of modern Muslim thinkers, including Arkoun, Soroush, al-Attas and Wadud.